(untitled) (Swiss Medical Weekly, 2022)
INTRODUCTION: This study explores general practitioners’ (GPs’) and medical specialists’ perceptions of role distribution and collaboration in the care of patients with chronic conditions, exemplified by spinal cord injury. METHODS: Semi-structured interviews with GPs and medical specialists caring for individuals with spinal cord injury in Switzerland. The physicians we interviewed were recruited as part of an intervention study. We used a hybrid framework of inductive and deductive coding to analyse the qualitative data. RESULTS: Six GPs and six medical specialists agreed to be interviewed. GPs and specialists perceived the role of specialists similarly, namely as an expert and support role for GPs in the case of specialised questions. Specialists’ expectations of GP services and what GPs provide differed. Specialists saw the GPs’ role as complementary to their own responsibilities, namely as the first contact for patients and gatekeepers to specialised services. GPs saw themselves as care managers and guides with a holistic view of patients, connecting several healthcare professionals. GPs were looking for relations and recognition by getting to know specialists better. Specialists viewed collaboration as somewhat distant and focused on processes and patient pathways. Challenges in collaboration were related to unclear roles and responsibilities in patient care. CONCLUSION: The expectations for role distribution and responsibilities differ among physicians. Different goals of GPs and specialists for collaboration may jeopardise shared care models. The role distribution should be aligned according to patients’ holistic needs to improve collaboration and provide appropriate patient care.